“I saw Othello’s visage in his mind”, or “White Mask, Black Handkerchif”: Satoshi Miyagi’s Mugen-Noh Othello and Translation Theory - Motohashi, Ted (Multicultural Shakespeare: Translation, Appropriation and Performance, 2016)
This paper tries to detect key elements in the translated performance of Shakespeare by focusing on Satoshi Miyagi’s “Mugen-Noh Othello” (literally meaning “Dreamy Illusion Noh play Othello”), first performed in Tokyo by Ku=Nauka Theatre Company in 2005, and subsequently seen in New Delhi, having now acquired a classic status of renowned Shakespearean adaptation in a foreign language that bridges a gap between the traditional form of Noh and the modern stage-presentation.